Dispositivo curricular de controle: gerenciamento do risco e governamento da surdez no cenário educacional - Morgenstern, Juliane Marschall (2009)
The following dissertation, ¨Curricular device of control: Management of the risk and govern of the deafness in the educational scene¨ connects to the curriculum development in approach to a post structural access. On the rummage of this work, for such constructions the checkpoint was the referring possibilities the capture and invention of the deafness in the curricular scope, taken mainly from the studies of Michel Foucault. For such constructions the National Curricular Parameters were selected: curricular adaptations, that when compose a discursive conjuncture next to other documents, has made possible the governance of the deafness in the educational contemporary area. Amongst the conceptual tools that had tacked this dissertation, I detach the governance and the bio-politics, which had hallowed to the description and analysis of the resume as a device that has operated in the management and regulation of the deaf group, produced as a group of risk. In this way it is possible to verify the placed normalization processes in functioning for the gear of the inclusion, where the deafness is translated by the bias of the cultural plurality. Argument that stops taking care of the neoliberal government principles, strategies of malleability in the direction are delineated to keep the curricular functionality and to make possible the regulation in the control society. In this manner, how much bigger the capacity of the resume in make itself flexible, greater the capacity to be large in scope of its governance. Being thus, the resume in such a way answers to the liquefaction and transitoriness of the world after-modern, it produces how much it. In view of strategical the inclusive movement as imperative in the current context, the delineation of the deafness in the register of the diversity can be glimpsed as category submit of normalization. Thus, one invests on the deaf citizen-pupils biopoliticos mechanisms of regulation that place in practical prophylactic and preventive measures for containment of possible risks represented for the exclusion, discrimination, intolerance, amongst other situations. Finally, without intending to solve any tenseness of the education or the resume, I bring glances that lead to think about possibilities o escape in the regulation meshes, pointing with respect to the communion of diad to be able/freedom.